Multilingual Communication and Court Interpreting in Slovenia: Challenges and Perspectives - Kučiš, Vlasta; Šepec, Miha; Kaloh Vid, Natalia (University of Maribor Press, 2026)
This book focuses on court interpreting, an interesting and upgrowing area of research in translation studies as a relatively young interdisciplinary science. Court intepreting is compulsory in asylum proceedings, police interrogations, court hearings, and healthcare when foreign citizens are involved who do not speak or understand Slovenian as the official language. This increased interest stems from the fact that recently many countries which previously had limited experience with foreign citizens are now facing increasing economic migration, which poses certain challenges and requires appropriate language policies and additional training for court interpreters. Court interpreters are experts and specialists in multilingual mediation who act as intermediaries between the court as a state institution and foreign citizens who are unfamiliar with legal and regulatory proceedures and do not understand or speak the language of the judiciary, which is in our case Slovenian. This interdisciplinary book seeks ways and means to improve cooperation between court interpreters and legal experts. The discussion focuses on the establishment and development of intercultural legal interpreting clinics, which enable training and education of future interpreters and lawyers, and the results of research in the light of the international TRANSLaw project.